Molecular Topology of the Transit Peptide during Chloroplast Protein Import. Issue 8 (10th July 2018) - Richardson, Lynn G.L.; Small, Eliana L.; Inoue, Hitoshi; Schnell, Danny J.
Abstract : A site-specific cross-linking approach reveals the molecular topology of the transit peptide and its nucleotide-dependent movement within the chloroplast protein import channel. Abstract: Chloroplast protein import is directed by the interaction of the targeting signal (transit peptide) of nucleus-encoded preproteins with translocons at the outer (TOC) and inner (TIC) chloroplast envelope membranes. Studies of the energetics and determinants of transit peptide binding have led to the hypothesis that import occurs through sequential recognition of transit peptides by components of TOC and TIC during protein import. To test this hypothesis, we employed a site-specific cross-linking approach to map transit peptide topology in relation to TOC-TIC components at specific stages of import in Arabidopsis thaliana and pea ( Pisum sativum ). We demonstrate that the transit peptide is in contact with Tic20 at the inner envelope in addition to TOC complex components at the earliest stages of chloroplast binding. Low levels of ATP hydrolysis catalyze the commitment of the preprotein to import by promoting further penetration across the envelope membranes and stabilizing the association of the preprotein with TOC-TIC. GTP hydrolysis at the TOC receptors serves as a checkpoint to regulate the ATP-dependent commitment of the preprotein to import and is not essential to drive preprotein import. Our results demonstrate the close cooperativity of the TOC and TIC machinery at each stage of transit peptide recognition and membrane translocation during protein import.